2011
DOI: 10.1302/0301-620x.93b1.23941
|View full text |Cite
|
Sign up to set email alerts
|

Open reduction and internal fixation of a traumatic diastasis of the pubic symphysis

Abstract: The aim of this study was to review the number of patients operated on for traumatic disruption of the pubic symphysis who developed radiological signs of movement of the anterior pelvic metalwork during the first post-operative year, and to determine whether this had clinical implications. A consecutive series of 49 patients undergoing internal fixation of a traumatic diastasis of the pubic symphysis were studied. All underwent anterior fixation of the diastasis, which was frequently combined with posterior p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
2
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 25 publications
2
43
2
9
Order By: Relevance
“…Dahingegen wird die Indikationsstellung zur Materialentfernung kontrovers diskutiert [4,7,8,16,18,27,30]. Insbesondere findet sich in der Literatur bislang keine ausreichende Evidenz in Form von randomisierten kontrollierten Studien mit der Fragestellung der Implantatentfernung nach Beckenringfraktur.…”
Section: Diskussion Und Empfehlung Der Metallentfernung Am Vorderen Uunclassified
See 2 more Smart Citations
“…Dahingegen wird die Indikationsstellung zur Materialentfernung kontrovers diskutiert [4,7,8,16,18,27,30]. Insbesondere findet sich in der Literatur bislang keine ausreichende Evidenz in Form von randomisierten kontrollierten Studien mit der Fragestellung der Implantatentfernung nach Beckenringfraktur.…”
Section: Diskussion Und Empfehlung Der Metallentfernung Am Vorderen Uunclassified
“…Abb. 5; [8,16]). Im Bereich der Iliosakralfuge wird durch die Verschraubung die physiologische Gelenkbewegung im Sinne einer Arthrodese transfixiert, d. h. das überwiegend vertikale Bewegungsmuster der Amphiarthrose bei der Lastübertragung von der Wirbelsäu-le auf den Beckenring wird aufgehoben [5].…”
Section: Diskussion Und Empfehlung Der Metallentfernung Am Vorderen Uunclassified
See 1 more Smart Citation
“…They also found an unexpectedly high rate of fixation failure with loss of reduction of 22% for isolated APC II pelvic ring injuries treated with anterior multiple-hole plate fixation alone [19]. Putnis et al [15] also found six of 43 patients treated surgically for APC injuries had anterior fixation failure and loss of reduction; all of these were APC II injuries treated with isolated anterior fixation and no posterior iliosacral screws. The role for posterior pelvic fixation with APC II pelvic fractures remains unclear and debated [18].…”
Section: Limitationsmentioning
confidence: 96%
“…Failure of open reduction and internal fixation of diastasis symphysis as a result of trauma was described by Putnis et al 11 Fifteen patients (31%) experienced anterior shifting of plate or screw, 10 patients experienced screw loosening or damage. Anterior fixation alone was the most frequent cause of treatment failure (n=7; 47%), followed by anterior fixation with unilateral sacroiliac fixation (n=6; 40%) and bilateral sacroiliac fixation (n=2; 13%).…”
mentioning
confidence: 95%